2017
DOI: 10.1590/s1980-6574201700si0077
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recall bias of information on soccer injuries in adolescents

Abstract: Aims: to analyze the recall bias of injury characteristics, anthropometric variables, and training variables in a morbidity survey in adolescent soccer players for a period of four months. Method: cohort study with 198 adolescent male soccer players, divided into two parts: a prospective study over four months, followed by a retrospective study. A morbidity survey containing personal and training data, in addition to information on injuries and their characteristics (anatomical site, mechanism, nature, moment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several publications have questioned the accuracy of self-reported injury studies. 4 , 20 , 36 A comparison of prospective and retrospective injury studies in Australian rules football over a 12-month period showed that recall accuracy significantly declines at 1 year. 16 Only 80% of the athletes were able to remember the number of injuries and the particular body parts involved.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have questioned the accuracy of self-reported injury studies. 4 , 20 , 36 A comparison of prospective and retrospective injury studies in Australian rules football over a 12-month period showed that recall accuracy significantly declines at 1 year. 16 Only 80% of the athletes were able to remember the number of injuries and the particular body parts involved.…”
Section: Discussionmentioning
confidence: 99%
“…A civilian TBI (Sherer et al, 2015) study showed that most participants self-reported longer LOC (66%) and PTA (84%) durations than medical records, potentially impacting diagnostic accuracy (e.g., moderate-to-severe TBI). Similarly, athletes with orthopedic injuries are more accurate in reporting on global information, such as whether or not they had an injury, rather than reporting specifics, such as injury location and even diagnoses (Gabbe, Finch, Bennell, & Wajswelner, 2003;Vanderlei et al, 2017). Indeed, several factors may affect reliability, such as time since injury, biases in recall (e.g., good old days), and the severity of the head injury and impact on memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that test-retest reliability coefficients would be higher for binary (presence vs. absence) and categorical characterization of injury characteristics relative to self-reported durations (Gabbe et al, 2003;Sherer et al, 2015;Vanderlei et al, 2017). Multiple statistical techniques were used to quantify test-retest reliability due to non-normality (Mayer et al, 2020) and the different distributions of data types (binary vs. categorical vs. continuous).…”
Section: Introductionmentioning
confidence: 99%
“…While several injury epidemiology researchers have used strategies to assess and manage information bias,13–15 few have appropriately accounted for confounding and censoring in longitudinal research efforts. This is because longitudinal studies contain time-varying covariates which may simultaneously be confounders and intermediates; analysis techniques that condition on past exposure and confounder history fail to account for such joint effects 16–18.…”
Section: Introductionmentioning
confidence: 99%